Classroom management problems and strategies used in large classes of secondary schools around Kota Samarahan, Sarawak - Ida Surnaya, Ahmad. (Universiti Malaysia Sarawak, UNIMAS, 2008)
The purpose of this research was to find out on types of classroom management problems that teachers regularly encounter during teaching and learning process of the large classes. For many years teachers had complained on the increasing of the problems especially in the large classes occupied by low abilities students. For many of them, they have to undergo the streaming process when they reached at the age of 16. In view of this, by doing the research, I investigated on types and the effectiveness of strategies used whether they were suitable to be implemented to overcome the problem of new generations. This paper reports on the results of a survey researched that involving 100 teachers in three selected school around Kota Samarahan. It was found that class sizes had contribute to the increasing of classroom management problem. Results from the fin dings indicated that variables, classroom management problems and effectiveness of strategies used had a connection with class size. Implications are discussed in terms of minimizing the appearances of classroom management problems using appropriate strate gies for a smooth teaching and learning process of large classes as well as a guideline for new teachers in the future.